A New P System Based Genetic Algorithm - Caiping Hou; Xiyu Liu (Institute of Advanced Engineering and Science, 2016)
For the “early convergence” or the “genetic drift” of the genetic algorithm, this paper proposes a new genetic algorithm based on P system. Based on the parallel mechanism of P system in membrane computing, we put forward the new P system based genetic algorithm (PBGA). So that we can improve the performance of GA.